มาตรการบังคับทางกฎหมาย กรณีผู้ขับขี่ขับรถในขณะเมาสุรา ตามพระราชบัญญัติจราจรทางบก พ.ศ. 2522 Compulsory Legal Cases of the Driver While Driving Drunk According to the Road Traffic Act B.E. 2522 - ยอดสุรางค์ พงศ์ปิยะ (Academic Journal Phranakhon Rajabhat University, 2017)
บทคัดย่อ ดุษฎีนิพนธ์ฉบับนี้มีวัตถุประสงค์ เพื่อการศึกษาแนวความคิดเกี่ยวกับมาตรการบังคับทางกฎหมายการลงโทษ การแก้ไข ปรับปรุง และการตรากฎหมาย เพื่อบังคับทางกฎหมายกับผู้ขับขี่ขับรถในขณะเมาสุราตามพระราชบัญญัติจราจรทางบก พ.ศ. ๒๕๒๒ รวมถึงศึกษากฎหมายของต่างประเทศ เพื่อนำมาเป็นแนวทางในการปรับปรุง แก้ไขกฎหมายจราจรทางบกของประเทศไทยที่ยังเป็นปัญหาข้อเท็จจริง ได้แก่ ปัญหาผู้ขับขี่ไม่ให้ความร่วมมือกับพนักงานเจ้าหน้าที่ที่ตรวจวัดหาระดับแอลกอฮอล์ในเลือด โดยอ้างว่าตนเองไม่ได้เมาสุรา หรือการตั้งจุดตรวจปฏิบัติไม่ถูกต้องตามระเบียบหลักการตั้งจุดตรวจ รวมทั้งประเด็นข้อกฎหมาย ได้แก่ ปัญหาการบังคับใช้กฎหมายตามพระราชบัญญัติจราจรทางบก พ.ศ. ๒๕๒๒ กรณีผู้ขับขี่ขับรถในขณะเมาสุรา มาตรการลงโทษผู้ขับขี่ขับรถในขณะเมาสุรา ปัญหาผู้ขับขี่ไม่ยินยอมตรวจวัดแอลกอฮอล์ โดยผู้ขับขี่ยินยอมเสียค่าปรับในข้อหา ฝ่าฝืนคำสั่งเจ้าพนักงานจราจร พนักงานสอบสวน หรือพนักงานเจ้าหน้าที่ ไม่ได้กำหนดเวลาการกักตัวผู้ขับขี่ที่แน่นอน ชัดเจน ปัญหากฎหมายสองฉบับให้อำนาจพนักงานสอบสวนไม่เท่ากัน ซึ่งจากการศึกษากฎหมายที่เกี่ยวข้องกับการจราจร และเสนอประเด็นเพิ่มเติม อาจเป็นอีกแนวทางหนึ่งในการปฏิบัติงานของเจ้าพนักงานจราจร พนักงานสอบสวน หรือพนักงานเจ้าหน้าที่ ซึ่งจะมีผลในการลดปัญหาการเกิดอุบัติเหตุจราจรที่เป็นสาเหตุหลักจาการขับขี่รถในขณะเมาสุรา โดยมีวิธีการศึกษาวิจัยเชิงเอกสารเชิงคุณภาพ ได้แก่ ( ๑ ) การศึกษาวิจัยเชิงเอกสาร เป็นการศึกษาจากเอกสาร ตำรา บทความ ภายในประเทศและต่างประเทศ (๒) การศึกษาวิจัยเชิงคุณภาพ เป็นการสัมภาษณ์ โดยใช้แบบสอบถามที่ได้มีการออกไปสัมภาษณ์จริง ตามกลุ่มตัวอย่างต่าง ๆ ที่เกี่ยวข้องกับงานวิจัย เพื่อเป็นข้อมูลสนับสนุนการศึกษาและวิเคราะห์ข้อมูลหลักที่ให้ได้ผลการวิจัยในเชิงความคิดเห็นของผู้ที่เกี่ยวข้องในภาคปฏิบัติตามบริบทของสังคมไทยได้อย่างถูกต้องตรงไปตรงมาเป็นอิสระในการให้คำตอบและเสนอความคิดเห็นเพิ่มเติมอันมีเนื้อหาที่ตรงประเด็นกับหัวข้อในงานวิจัยอันจะยังผลให้เกิดผลงานวิจัยที่มีผลเป็นจริงมากที่สุด เพื่อนำมาใช้ในการสนับสนุนข้อมูลในประเด็นข้อเท็จจริงและประเด็นข้อกฎหมายจากการศึกษาสรุปว่า พระราชบัญญัติจราจรทางบก พ.ศ. ๒๕๒๒ มาตรา ๔๓(๒) “ ผู้ขับขี่ขับรถในขณะเมาสุรา ” มีปัญหาในการบังคับใช้กฎหมายมาก จึงควรมีการปรับปรุง แก้ไข เพิ่มเติม เทคนิคด้านกฎหมาย ให้สามารถสอดรับกับการเปลี่ยนแปลงของระบบเทคโนโลยีที่ก้าวหน้า ทันสมัยทัดเทียมกับนานาอารยะประเทศ ตลอดจนให้ทันต่อการปรับปรุงกฎหมายฉบับอื่น ๆ ที่มีการแก้ไขอยู่เป็นประจำ เพื่อความถูกต้องและยุติธรรมกับทุกฝ่าย ไม่ว่าจะเป็นผู้ขับขี่ หรือ เจ้าพนักงานจราจร พนักงานสอบสวน หรือพนักงานเจ้าหน้าที่ ซึ่งเป็นผู้บังคับใช้กฎหมายโดยตรง ซึ่งมีข้อควรแก้ไขปรับปรุง ดังต่อไปนี้ มาตรการทางกฎหมาย ได้แก่ (๑) ตามพระราชบัญญัติจราจรทางบก พ.ศ. ๒๕๒๒ มาตรา ๔๓ (๒) “ ผู้ขับขี่ขับรถในขณะเมาสุรา ” เป็นเหตุให้ผู้อื่นถึงแก่ความตายโดยประมาท ตามประมวลกฎหมายอาญา มาตรา ๒๙๑ ควรปรับเปลี่ยนข้อหาเป็น “ ฆ่าผู้อื่นโดยไม่เจตนา ” ตามประมวลกฎหมายอาญา มาตรา ๒๙๐ (๒) ควรที่จะลดค่าปริมาณแอลกอฮอล์ในเลือด โดยกำหนดเกณฑ์ตามอายุของผู้ขับขี่ที่มีอายุต่ำกว่า ๒๐ ปี ผู้ได้รับใบอนุญาตขับขี่ครั้งแรก ผู้ขับขี่รถจักรยานยนต์ ผู้ขับขี่รถสาธารณะ รถโรงเรียน รถบรรทุก ควรมีปริมาณแอลกอฮอล์ในเลือดได้ไม่เกิน ๒๐ มิลลิกรัมเปอร์เซ็นต์ (๓) ผู้ขับขี่ที่ไม่ยินยอมเข้าทำการทดสอบเพื่อหาค่าปริมาณแอลกอฮอล์ในเลือด โดยวิธีเป่าลมหายใจ ( Breath Analyzer Test ) โดยวิธีตรวจวัดจากปัสสาวะ หรือตรวจวัดจากเลือด ควรจะมีการแก้ไขโทษปรับให้มีโทษสูงขึ้น และควรตรวจวัดแอลกอฮอล์เพียงครั้งเดียว (๔) การกักตัวผู้ขับขี่เพื่อเข้าทำการทดสอบหาค่าปริมาณปริมาณแอลกอฮอล์ในเลือดควรกำหนดเวลาไว้ไม่เกิน ๒ ชั่วโมง หากเกิน ๒ ชั่วโมง ควรปล่อยตัวผู้ขับขี่ไปทันที โดยไม่มีเงื่อนไขใด ๆ ทั้งสิ้น (๕) ผู้ขับขี่ที่ไม่ยินยอมเข้ารับการทดสอบเพื่อหาค่าปริมาณแอลกอฮอล์ในเลือด โดยไม่มีเหตุผลอันสมควร ให้ใช้บทสันนิษฐานเบื้องต้นว่าเป็นผู้ที่มีปริมาณแอลกอฮอล์ในเลือดเกินกว่าที่กฎหมายกำหนด (๖) เกี่ยวกับสิทธิเสรีภาพส่วนบุคคล เมื่อมีการตั้งจุดตรวจ จุดสกัด เจ้าพนักงานจราจร พนักงานสอบสวน หรือพนักงานเจ้าหน้าที่ ควรมีเครื่องทดสอบแอลกอฮอล์เบื้องต้นโดยไม่ต้องให้ผู้ขับขี่ลงจากรถ หากไม่พบปริมาณแอลกอฮอล์ในเลือด ก็ให้ผู้ขับขี่ขับรถต่อไปได้ หากพบปริมาณแอลกอฮอล์ในเลือดควรเชิญผู้ขับขี่ลงจากรถเพื่อเข้าทำการทดสอบกับเครื่องตรวจวัดแอลกอฮอล์ต่อไป (๗) อัตราโทษตามมาตรา ๔๓ (๒) “ ผู้ขับขี่ขับรถในขณะเมาสุรา ” ควรมีอัตราโทษที่เพิ่มสูงขึ้น ดังนี้ “ ผู้ใดฝ่าฝืนมาตรา ๔๓(๒) ต้องระวางโทษจำคุกไม่เกิน ๒ ปี หรือปรับตั้งแต่ ๒๐,๐๐๐-๔๐,๐๐๐ บาท หรือทั้งจำทั้งปรับ และพักใบอนุญาตขับขี่ มีกำหนดไม่น้อยกว่า ๑ ปี หรือเพิกถอนใบอนุญาตขับขี่ มาตรการเสริม ได้แก่ (๑) ควรบัญญัติกฎหมายเพิ่มเติมให้ผู้ขับขี่ติดตั้งอุปกรณ์เครื่องป้องกันผู้ขับขี่ขับรถในขณะเมาสุรา (Ignition Interlock Device) กับผู้ที่เคยกระทำผิดข้อหา “ ผู้ขับขี่ขับรถในขณะเมาสุรา ” (๒) ควรเพิ่มเติมข้อหาปฏิเสธการตรวจวัดแอลกอฮอล์ไว้โดยตรง ไม่ต้องไปเลี่ยงตั้งข้อหา “ ฝ่าฝืนคำสั่ง ” (๓) ควรบัญญัติกฎหมายเพิ่มเติมตามพระราชบัญญัติจราจรทางบก พ.ศ. ๒๕๒๒ เรื่อง การมีเครื่องดื่มที่มี แอลกอฮอล์ภาชนะถูกเปิดออกไว้ในครอบครองในยานพาหนะ (๔) ควรจัดตั้งศาลจราจร เพื่อพิจารณาคดีตามพระราชบัญญัติจราจรทางบก พ.ศ. ๒๕๒๒ เพื่อแบ่งเบาภาระการพิจารณาคดีของศาลอาญาต่าง ๆ (๕) ในช่วงเทศกาลสำคัญต่าง ๆ เช่น วันปีใหม่ วันสงกรานต์ ผู้ขับขี่ที่รับการตรวจวัดแอลกอฮอล์ที่จุดตรวจใด ควรให้สลิปการตรวจวัดพร้อมลงลายมือชื่อ ยศ ตำแหน่ง วัน เวลา สถานที่ตรวจวัด พร้อมทั้งให้ผู้ขับขี่ลงลายมือชื่อ หมายเลขประจำตัวประชาชน ๑๓ หลัก มอบให้กับผู้ขับขี่ เพื่อแสดงให้กับเจ้าหน้าที่จุดตรวจต่อไปตรวจสอบได้ Abstract The objective of this dissertation is study the concept of compulsory legal penalties for amendment and enactment, in order enforce the laws against the driver driving while intoxicated, according to the Road Traffic Act B.E. 2522. The study of international law be used as guidelines for improvement. Amendments to the Law on Road Traffic is also an issue of fact and the riders did not cooperate with the officer determined the blood alcohol level Claiming that he was not drunk. Or the checkpoints violate the regulations, principles checkpoints. Including legal issues, including the enforcement of the Road Traffic Act B.E. 2522 If a motorist driving while drunk. Penalties for driving while drunk. Alcohol problems, the driver does not consent. The driver agrees to pay the charges. Disobeyed traffic officer inquiry official or the competent Not scheduled to detain the driver, of course, the second edition of the law authorizing officers are not equal. The study on the traffic laws. And suggest additional issues It is another way in the performance of official traffic. inquiry official or the competent This has the effect of reducing traffic accidents are the main causes from driving while drunk. The method of qualitative research papers include: (1) education research papers. The study of texts, articles, documents, domestic and foreign. (2) study of qualitative research. interviews The questionnaire, which has issued the actual interview. Based on a sample of related research. To support the analysis of data provided by the findings in the comments of those involved in the practical context of social Thailand.Correctly, frankly, feel free to answer And offer additional comments that have content that is relevant to the topic of the research will also contribute to research the effect is most true. To be used in support of the issues, facts and legal issues, the study concluded. The Road Traffic Act B.E. 2522, Section 43 (2) "driving while intoxicated" is a problem of law enforcement. It should be a legal modification techniques. To cope with the change of technology. Modern civilized nations with equal And keep up-to-update law that is modified on a regular basis. For an accurate and fair to all parties. Whether a rider or traffic official. inquiry official or the competent The law enforcement directly. Which has to be modified as follows. Legal measures are: (1) According to the Road Traffic Act B.E. 2522, Section 43 (2) "driving while intoxicated" and caused the death of another through negligence. Section 291 of the Criminal Code Should modify the charges as "kill others without willful" under the Criminal Code, Section 290 (2) should reduce the amount of alcohol in the blood. The criteria in the age of the driver under the age of 20 years. Who was the first driver’s license -3- Motorcyclist The driving public buses, trucks should have a blood alcohol content is less than 20 mg per cent. (3) the driver does not consent to a test to determine blood alcohol content. By breath (Breath Analyzer Test). By measurement of urinary Or measurement of blood There should be a fixed penalty fines to be increased. Alcohol and preferably only once. (4) the detention of the driver to be tested for the amount of alcohol in the blood should be scheduled no more than 2 hours but if more than 2 hours, the driver should be released immediately. Without any condition (5) the driver does not consent to take the test to determine blood alcohol content. By unreasonably Use a basic assumption that people with blood alcohol content over the legal limit. (6) On the right to personal liberty. When an officer makes a traffic checkpoints. inquiry official or the competent Should have a preliminary alcohol test without the driver in the car. If there’s no amount of alcohol in the blood. It allows the driver to continue driving it. If you find your blood alcohol content should invite the driver of getting the car in order to test the detector to alcohol. (7) by section 43 (2) "driving while intoxicated" should be taken to increase the rate. "Any person who contravenes section 43 (2) shall be punished with imprisonment not exceeding two years or a fine of. 20,000-40,000 baht, or both. And suspended license a period not less than one year or revoked license. Supplementary measures include (1) the law further allows the driver to install equipment to prevent motorists driving while intoxicated (Ignition Interlock Device).Those who had criminal charges "Motorists driving while intoxicated" (2) should also denied charges of Alcohol directly. Not need to be charged "Disobedience" (3) should be further legislation under the Road Traffic Act B.E. 2522, have a drink with. Open container of alcohol was in possession of the vehicle. (4) should establish a traffic court. To consider the case under the Road Traffic Act B.E. 2522, to ease the burden of the trial court. (5) During major festivals such as New Year’s Day riders tested for alcohol at any checkpoint. Slip-measurement should be ready to sign. Dressing for the measurement takes place. And the driver signature. 13-digit identification number given to the driver. To illustrate this point, the authorities continue to investigate. Key word: Compulsory Legal Cases of the Driver While Driving Drunk According to the Road Traffic Act B.E. 2522.